Aluminium ions inhibit the formation of diacylglycerol generated by phosphatidylcholine-hydrolysing phospholipase C in tobacco cells - Pejchar, Premysl; Potocký, Martin; Novotná, Zuzana; Veselková, Stepánka; Kocourková, Daniela; Valentová, Olga; Schwarzerová, Katerina; Martinec, Jan (The New phytologist, 2010)
• Aluminium ions (Al) have been recognized as a major toxic factor for crop production in acidic soils. This study aimed to assess the impact of Al on the activity of phosphatidylcholine-hydrolysing phospholipase C (PC-PLC), a new member of the plant phospholipase family. • We labelled the tobacco cell line BY-2 and pollen tubes with a fluorescent derivative of phosphatidylcholine and assayed for patterns of fluorescently labelled products. Growth of pollen tubes was analysed. • We observed a significant decrease of labelled diacylglycerol (DAG) in cells treated with AlCl(3). Investigation of possible metabolic pathways that control DAG generation and consumption during the response to Al showed that DAG originated from the reaction catalysed by PC-PLC. The growth of pollen tubes was retarded in the presence of Al and this effect was accompanied by the decrease of labelled DAG similar to the case of the BY-2 cell line. The growth of pollen tubes arrested by Al was rescued by externally added DAG. • Our observation strongly supports the role of DAG generated by PC-PLC in the response of tobacco cells to Al.
Keywords: diglyceridy; časové faktory; Phosphatidylcholines; Pollen Tube; fosfatidylcholiny; Cell Membrane; pylová láčka; Aluminum; tabák; porfobilinogen; viabilita buněk; Time Factors; Type C Phospholipases; Diglycerides; ionty; Nicotiana; buněčná membrána; hliník; Cell Survival; Ions; Porphobilinogen; fosfolipasy typu C